2017
DOI: 10.1016/j.socscimed.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Assessing physician productivity following Norwegian hospital reform: A panel and data envelopment analysis

Abstract: Our measures of physician productivity declined from 2001 to 2013. More support staff was a significant variable for predicting physician productivity. Personnel mix developments in the study period were unfavorable with respect to physician productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 72 publications
0
21
0
1
Order By: Relevance
“…A recent study conducted by Johannessen et al (2017), investigated the impact of several political reforms of the Norwegian hospital sector occurred since 2002. All public hospitals were transferred from a system of county ownership to central government ownership.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study conducted by Johannessen et al (2017), investigated the impact of several political reforms of the Norwegian hospital sector occurred since 2002. All public hospitals were transferred from a system of county ownership to central government ownership.…”
Section: Discussionmentioning
confidence: 99%
“…In so doing, the government expected to increase hospital efficiency by providing greater autonomy with respect to planning, budgeting and workforce policies of the health units (Hagen and Kaarboe, 2006). Johannessen et al (2017) used a non-parametric DEA model and panel analyses to study the overall physician productivity. Their results showed that, in spite of comprehensive governmental efforts, there was a significant variation in productivity among the country's hospitals, along with a noticeable decline in physician productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than analysing changes at macro level, Johannessen et al, (13) analysed the effects of the reforms on the labour levels between 2001 and 2013. They found that that in general, the number of patients treated increased by 47% and DRG scores increased by 35%, indicating that more and sicker patients were being treated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The DEA method was first proposed by Charnes et al [12] as a mathematical programming method to evaluate the relative efficiency of decision-making units (DMUs) with multiple inputs and outputs variables. Although some papers have used the DEA method to solve productivity-related issues, no research utilized this method to deal with the evaluation of dredging productivity [13][14][15][16][17]. This paper extends the DEA method to propose a novel dredging productivity evaluation method, solving the issues that are related to the evaluation of dredging productivity.…”
Section: Introductionmentioning
confidence: 99%